PENCAPAIAN PENDISTRIBUSIAN BARANG MELALUI JUMLAH ARMADA DAN RITASE - Sarinah Sarinah; Raden Muhammad Eko Mulia Rezki (Institut Transportasi dan Logistik Trisakti, 2016)
The Company is service transporting of palm oil, cement and fertilizer is domiciled in Belawan, Medan. In this study, to determine the development of fleet size, ritase, and achieving distribution of goods in the region of Belawan. Method is use quantitative methods, while, to know the effect of fleet size and the number of ritase in achieving distribution of goods as indicated by multiple linear regression line, namely; Y = 156 400 - 7.726X1 + 25.033X2, Meanwhile, determinant coefficient test showed 0.995, suggesting the contribution of fleet size and the number of ritase to the achievement of the distribution of goods amounted to 99.5% while the rest influenced by other factors. Furthermore, the test Simultaneous results F count equal to 2239.989 for the F table at 3:47 Then F count> F table (2239> 3.47) then H0 is rejected, it means that with the same significant difference between the fleet and the number of ritase towards achieving the delivery of goods.